2017
DOI: 10.18632/oncotarget.20971
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between genetic polymorphisms in metabolic enzymes and longer leukocyte telomere length induced by omethoate

Abstract: PurposeThis study aimed to explore the effects of genetic polymorphisms in metabolic enzymes on relative telomere length changes and explore the mechanism of canceration induced by omethoate.Materials and Methods180 long-term omethoate-exposed workers and 115 healthy controls were recruited. Real-time PCR method was applied to determine the relative telomere length in peripheral blood leukocytes DNA, and Six polymorphic loci of GSTT1(+/−), GSTM1(+/−), GSTP1 rs1695, CYP2E1 rs6413432, CYP2E1 rs3813867 and PON2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The International Agency for Research on Cancer (IARC) has assessed several pesticides as possible human carcinogens (Teodoro et al, 2019). Many pieces of research carried out regarding the side effects of organophosphorus compounds discovered some human disorders, such as neurological, neurobehavioral, reproductive problems as well as malignancies, all are caused by chronic exposure to a low dose of OPs (Duan et al, 2017). Therefore, researchers found that the genotoxic tests achieve results more accurately for chronic poisoning and early identification than results achieved by acetylcholinesterase-inhibition tests that are commonly conducted under severe exposure (Chandrakar et al, 2020 .…”
Section: Introductionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) has assessed several pesticides as possible human carcinogens (Teodoro et al, 2019). Many pieces of research carried out regarding the side effects of organophosphorus compounds discovered some human disorders, such as neurological, neurobehavioral, reproductive problems as well as malignancies, all are caused by chronic exposure to a low dose of OPs (Duan et al, 2017). Therefore, researchers found that the genotoxic tests achieve results more accurately for chronic poisoning and early identification than results achieved by acetylcholinesterase-inhibition tests that are commonly conducted under severe exposure (Chandrakar et al, 2020 .…”
Section: Introductionmentioning
confidence: 99%